Kualitas Organoleptik Daging Kambing Lokal dengan Lama Pelayuan dan Cara Pemasakan yang Berbeda (Sensoring Quality of Lokal Goat Meat as Influenced by Different Length of Conditioning and Types of Cooking) - Harapin Hafid; Adnan Syam (Buletin Peternakan, 2009)
The aim of this research was to study the effect of different length of conditioning time and types of cooking on sensory quality of meat from goats under traditional way of keeping in remote villages. The result of this research would lead to the ability to decide the better conditioning processes post slaughtering to increase meat quality. The research was done following a completely randomized design of 4x2 factorial, each combination of experimental treatment had three replications. The first factor was the length of conditioning (A), which were consisted of without conditioning (A0), three hour conditioning (A1), six hour conditioning (A2), and nine hour conditioning (A3). The second factor was the types of cooking (B) which were cooking by boiling (A1), and cooking by roasting (A2). Theresult from a panel test indicated that conditioning processes for nine hours had capable of increasing quality of local native goat meat especially on aroma, flavor, juiciness, and final pH, mean while in the case of tenderness it did notshow any affect of different length of conditioning and types of cooking. Better quality would be obtained when conditioning was done for nine hours in side refrigerator.(Key words: Goat meat conditioning, Type cooking, Sensory quality)